2011
DOI: 10.5194/acp-11-1813-2011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of meteorology on PM<sub>10</sub> trends and variability in Switzerland from 1991 to 2008

Abstract: Abstract. Measurements of airborne particles with aerodynamic diameter of 10 µm or less (PM 10 ) and meteorological observations are available from 13 stations distributed throughout Switzerland and representing different site types. The effect of all available meteorological variables on PM 10 concentrations was estimated using Generalized Additive Models. Data from each season were treated separately. The most important variables affecting PM 10 concentrations in winter, autumn and spring were wind gust, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(137 citation statements)
references
References 49 publications
14
119
0
4
Order By: Relevance
“…Since the year 2000, however, the PM 10 concentrations in Germany seem to stagnate, and feature some mere inter-annual fluctuations (UBA, 2009). A similar stagnation of PM 10 since 2000 has also been reported for other areas in Europe, such as the UK , Switzerland (Barmpadimos et al, 2011), Belgium, Czech Republic, Italy and Norway. This is in notable contrast to the continued reductions in PM emissions.…”
Section: Introductionmentioning
confidence: 62%
“…Since the year 2000, however, the PM 10 concentrations in Germany seem to stagnate, and feature some mere inter-annual fluctuations (UBA, 2009). A similar stagnation of PM 10 since 2000 has also been reported for other areas in Europe, such as the UK , Switzerland (Barmpadimos et al, 2011), Belgium, Czech Republic, Italy and Norway. This is in notable contrast to the continued reductions in PM emissions.…”
Section: Introductionmentioning
confidence: 62%
“…A method to control or take into account meteorology effects on pollutant concentrations involves the development and use of predictive statistical models (Lou Thompson et al, 2001;Carslaw et al, 2006;Beevers et al, 2009;Carslaw and Priestman, 2015;Fuller and Carslaw, 2017). Such models attempt to use a number of explanatory variables such as surface measurements of wind behaviour, atmospheric temperature, and pressure to explain the variability of pollutant concentrations.…”
Section: Meteorological Normalisationmentioning
confidence: 99%
“…When the six site type trends were aggregated together, the stronger decreasing trend for traffic sites was clear with an average trend of -0.77 µg m ( Figure 5). Barmpadimos et al (2011) also reported trends based on site type but their site type definitions were not the same as used in this study so they should not be directly compared. The higher first four points in the rural panel of Figure 5 was caused by 5 the aggregated time series only containing the Magadino-Cadenazzo monitoring site at the very beginning of analysis period.…”
Section: Random Forest Model Evaluationmentioning
confidence: 99%